James Edward Keirans (1935–2023): A Bibliography, Described Taxa and Eponyms/Patronyms - Robbins, Richard G.; Durden, Lance A. (Zootaxa, 2024)
A bibliography is provided of the 228 scientific publications authored by James E. Keirans, a prominent American tick taxonomist and medical entomologist, together with chronologically organized lists of the tick taxa that he described and the eponyms and patronyms named in his honor.